The Mediator's Hand Book - Beer, Jennifer E. (New Society, 2012)
The popular The Mediator's Handbook presents a time-tested, adaptable model for helping people work through conflict. Extensively revised to incorporate recent practice and thinking, the accessible manual format lays out a clear structure for new and occasional mediators while offering a detailed, nuanced resource for professionals.
Includes index
Keywords: Mediation